A gente só olha o presente... nunca se olha o passado: as comunidades quilombolas pelo discurso do outro - Kaspreski, Renata dos Santos (2020)
This is a qualitative studythat has as the main objective to investigate the discourses present in the city of Palmas-PR about the communitiesofquilombolas remnantslocated in Palmas-PRand their rights. This investigation takes into account the specific objectives of this research, which areto realizehow these representations are shaped in a set of discursive formations; to understand what this set of enunciationscarries about history, prejudice, stigma, ideologies and power relations; to verify if the discursive structures are related to the real of the communities of quilombolas remnants; to make a bibliographical survey on the trajectory of the communities located in Palmas and on how the Brazilian legal system deals with the quilombola issue. The corpusof analysis was generated through structured interviews, with an open degree of structuring, so the interviewees could express themselves freely(GIL, 2008). People from the Palmense community were invited to be the researchedparticipants, regardless of gender or age.Passers-by overwhelmed by history were intercepted in some locations in the city, such as the central region and neighborhoods near downtown, commercial establishments and in a public higher education institution. The data were analyzed using the theoretical support of the Discourse Analysis and Cultural Studies.As a result of this research, it hinder was found that the speeches of the participants were guided by discursive formations that contribute to erase, to silence or to deny the quilombola history. The data also enable to affirm that quilombola rights, in general, are neglected by the Palmense community because they are both inscribed in a structurally racist ideology and in an ideology that defends capital as priority. This research work contributes to reflect on how these discourses affect these communities, spreadideologies and prejudices, restrict opportunities and hinder thequilombola struggle for their rights, furthermore it is an importantopportunity to show the history of a group overwhelmed by history and fundamental in the construction of the country.